1982
DOI: 10.2337/diacare.5.2.s140
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Human Insulin (recombinant DNA) in Diabetic Subjects Pretreated with Pork or Beef Insulin: First Results of a Multicenter Study

Abstract: In two double-blind studies 66 insulin-dependent diabetic subjects pretreated with pork insulin were changed to human insulin (recombinant DNA) or a purified pork insulin preparation (regular and NPH insulin). Sixty-five patients previously pretreated with beef insulin were transferred, in a randomized, double-blind fashion, to human insulin and purified beef insulin of the same preparations (regular and NPH insulin). Patients' metabolic control, as demonstrated by fasting and 1-h postprandial blood glucose, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…All but one[61] provided data on hypoglycaemic events, this study simply reporting no events during the investigation. Four studies found no differences in the frequency of hypoglycaemia[2–64]. Two studies reported a statistically insignificantly increased frequency of hypoglycaemia in subjects on ‘human’ insulin as compared to those on insulin of animal origin[65–66].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All but one[61] provided data on hypoglycaemic events, this study simply reporting no events during the investigation. Four studies found no differences in the frequency of hypoglycaemia[2–64]. Two studies reported a statistically insignificantly increased frequency of hypoglycaemia in subjects on ‘human’ insulin as compared to those on insulin of animal origin[65–66].…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen publications[6–92] compare a period of animal insulin treatment to one of ‘human’ insulin treatment in the same subject. Nine of these studies[75–77,81–83,85–86,88–91] reported no difference between insulin species while a further three[78–79,92] found fewer hypogycaemic episodes with ‘human’ insulin and/or greater awareness of hypoglycaemia.…”
Section: Resultsmentioning
confidence: 99%
“…In Scandinavia, however, this should not be expected as all insulin is highly purified and insulin resitance due to insulin antibodies is extre¬ mely rare (3,6,7,12,16,24,29).…”
Section: Immunology and Antigenicitymentioning
confidence: 92%
“…Clinical pharmacology studies with recombinant human insulin produced by fermentation in E. coli (Humulin, Eli Lilly, Indianapolis) established bioequivalence of semisynthetic and recombinant Humulin formulations. 14 , 32 , 33 Extensive clinical studies were performed in patients with type 1 and type 2 diabetes 14 , 33 36 to confirm consistent clinical efficacy when transferring patients to the recombinant formulations. 14 , 33 , 34…”
Section: Humulin and Novolinmentioning
confidence: 99%